MEMBANGUN KEMANDIRIAN FINANSIAL PRIBADI DAN UMAT - Arsyianti, Laily Dwi; Beik, Irfan Syauqi (MIZAN: JOURNAL OF ISLAMIC LAW, 2013)
Life in the world not only involves compulsory worship but also social relations. Our interest in social relationships is to build a prosperous people in the world and in the Hereafter, as well as our task which has been determined as a vicegerent on earth. This article tries to explain the steps that need to be taken to develop the independence both personally and in the unity of the people, from the financial side. This financial capital which became one person and Muslims widely, to help the robustness of the buildings and the revival of the Ummah. Therefore, in the end we can stand on its own without depending on any party that can control us and may be misleading the people.